Developing Teacher Feedback on Written Work Within the Process Approach: One Way Of Improving the Students’ Composition - Marsuki Marsuki (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2020)
Issues in EFL and ESL have revealed that students’ performance in writing remain unsatisfactory although the teacher has tried to apply an appropriate technique as maximally as possible. This article discusses about how a teacher can develop feedback technique on Writing by applying the process approach as one way of improving the students’ composition. On the basis of the technique, there are two types techniques the teacher may apply in Writing by using the process approach, namely written comment and student-teacher conference. The use of both forms will simultaneously maximize the amount of feedback and the quality of feedback required for effective revision of the working draft. The appropriateness and accuracy of these techniques as matter of fact depend on several factors: ability, personality, and attitude of the teacher towards a particular technique, and the learners’ need, abilities, and attitude, the number of students in the class, and the time allotment in the actual teaching –learning situation. Consequently, the students need to be encouraged to see Writing as a means of learning rather than demonstrating learning. Furthermore, the teacher feedback activities will be seen as a vehicle to lead the learner towards the path of self feedback in the process of writing.